Should We Trust in Leading Indicators? Evidence from the Recent Recession - Katja Drechsel; Rolf Scheufele (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
The paper analyzes leading indicators for GDP and industrial production in Germany. We focus on the performance of single and pooled leading indicators during the pre-crisis and crisis period using various weighting schemes. Pairwise and joint significant tests are used to evaluate single indicator as well as forecast combination methods. In addition, we use an end-of-sample instability test to investigate the tability of forecasting models during the recent financial crisis. We find in general that only a small number of single indicator models were performing well before the crisis. Pooling can substantially increase the reliability of leading indicator forecasts. During the crisis the relative performance of many leading indicator models increased. At short horizons, survey indicators perform best, while at longer horizons financial indicators, such as term spreads and risk spreads, improve relative to the benchmark. – – Dieses Papier untersucht die Prognosegüte konjunktureller Frühindikatoren für das Bruttoinlandsprodukt sowie die Industrieproduktion in Deutschland vor und während der Krise. Die Prognosegüte einzelner und durch verschiedene Gewichtungsschemata kombinierter Prognosen basierend auf Frühindikatoren wird durch gemeinsame Signifikanztests bewertet. Des Weiteren geben End-of-sample Instabilitätstests Auskunft über die Stabilität der Prognosemodelle während der aktuellen Finanzkrise. Es wird gezeigt, dass nur wenige Einzelindikatoren vor der Krise genauere Prognosen liefern als das AR-Modell. Durch Kombination kann die Prognosegüte von Frühindikatoren erheblich verbessert werden. Während Umfragedaten für die Kurzfristprognose die Prognosegüte erheblich verbessern, liefern Finanzmarktdaten, wie bspw. Zinsspreads und Risikoaufschläge, bessere Prognosen als die Benchmark für längerfristige Prognosehorizonte.
urn:nbn:de:101:1-2010070679
Keywords: E37; C22; C53; 330; Leading Indicators; Forecast Evaluation; Forecast Pooling; Structural Breaks; Frühindikatoren; Prognosegüte; Prognosekombination; Strukturbrüche; Konjunkturindikator; Prognoseverfahren; Statistischer Test; Strukturbruch; Finanzmarktkrise; Wirtschaftskrise; Deutschland